PRESIDENTIAL SYSTEM OF GOVERNMENT IN INDONESIA: A COMPARATIVE STUDY WITH THE PARLIAMENTARY MODEL - Jona Bungaran Basuki Sinaga; Melyana R Pugu; Al-Amin (Prosiding Seminar Nasional Indonesia, 2024)
The government in Indonesia follows a presidential system that provides high executive stability. Elections are used to directly elect the nation's leaders and administration, ensuring consistency in national policy. However, political coalitions between the executive and legislative branches often lead to conflict especially when the two branches come from conflicting political parties. This can bring down the order of government. In contrast, the parliamentary model tends to prioritize harmony because the executive is elected from among the parliament and the two parties are always in line. However, Indonesia has devised a number of mechanisms that can minimize the shortcomings of the presidential model. The government coalition system and the checks and balances mechanism have effectively balanced the relationship between the branches of state. Constitutional provisions and regulations that are responsive to political dynamics also allow the presidential system to continue to adapt to various changes. Thanks to these efforts, the stability of governance in Indonesia has been maintained despite the challenges faced. In general, despite the fundamental differences between presidential and parliamentary systems, Indonesia has been able to effectively implement the presidential system through various adjustments in accordance with its socio-political context.